Synthesis, electrochemistry and electrocatalytic activity of cobalt phthalocyanine complexes - Effects of substituents for oxygen reduction reaction - Acar, Elif Turker; Tabakoglu, Tuba Akkizlar; Atilla, Devrim; Yüksel, Fatma; Atun, Gulten (Pergamon-Elsevier Science Ltd, 2018)
The synthesis, characterization, electrochemistry and electrocatalytic activity of the mono (pyridine-4-oxy)-tri (tert-butyl) phthalocyaninato Co(II) (Pc1) and mono (pyridine-4-oxy)-hexa (hexyl) phthalocyaninato Co(II) (Pc2) are reported here. One reversible and one irreversible oxidation couples and two quasi-reversible reduction couples are observed for two complexes on the cyclic voltammograms. Both cobalt phthalocyanine derivatives (CoPcs) and multiwall carbon nanotube (MWCNT) composite (CoPcs/MWCNT) electrodes are coated on glassy carbon electrodes and used as electrocatalysts for oxygen reduction reaction (ORR). The morphology of composite surfaces is characterized using Scanning Electron Microscope (SEM). The results obtained using rotating disk electrode (RDE) reveal that the high catalytic activity is observed with 4e(-) and mixed 2e(-) - 4e(-) ORR mechanisms for Pc1/MWCNT and Pc2/MWCNT hybrid catalysts in alkaline media, respectively. The tert-butyl substituent is more efficient with desired 4e(-) mechanism on the catalytic activity of the composite electrode compared to the hexyl substituent on the CoPc ring. Published by Elsevier Ltd.
Keywords: Cobalt phthalocyanine; Substituent group effect; Electrocatalytic activity; Oxygen reduction reaction; Multiwall carbon nanotube